2016
DOI: 10.4049/jimmunol.1502492
|View full text |Cite
|
Sign up to set email alerts
|

RIPK1 and PGAM5 Control Leishmania Replication through Distinct Mechanisms

Abstract: Leishmaniasis is an important parasitic disease found in the tropics and sub-tropics. Cutaneous and visceral leishmaniasis affect an estimated 1.5 million people worldwide. Despite its human health relevance, relatively little is known about the cell death pathways that control Leishmania replication in the host. Necroptosis is a recently identified form of cell death with potent anti-viral effects. RIPK1 is a critical kinase that mediates necroptosis downstream of death receptors and toll-like receptors. Heme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 44 publications
0
36
1
Order By: Relevance
“…We have previously demonstrated that induction of HO-1 favors Leishmania infantum replication and infection in human and murine macrophages by reduction of its leishmanicidal mechanisms, as nitric oxide and ROS ( 12 ). We have also described increased serum levels of HO-1 and total heme in VL patients compared to healthy endemic controls ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…We have previously demonstrated that induction of HO-1 favors Leishmania infantum replication and infection in human and murine macrophages by reduction of its leishmanicidal mechanisms, as nitric oxide and ROS ( 12 ). We have also described increased serum levels of HO-1 and total heme in VL patients compared to healthy endemic controls ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 59%
“…Human neutrophils were experimentally infected with L . infantum and incubated in the absence or presence of heme for 3 h. We have used 30 μM of heme in the experiments because this was the average level detected in serum from patients with VL ( 13 ), as similar to what has been described in malaria ( 25 , 26 ) and sickle cell disease ( 27 ). In addition, doses close to 30 µM have been commonly used in in vitro experiments published from other groups ( 8 , 9 , 28 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations